The Rolling Stones 50 : with over 1,000 illustrations in colour and black and white - Jagger, Mick
"This is our story of fifty fantastic years of the greatest rock 'n' roll band the world has ever known. ...Curated by us, it features the very best photographs and ephemera from our archives and beyond."--Dust jacket.